REGIONAL DEVELOPMENT PLANNING IN THE NATIONAL DEVELOPMENT PLANNING SYSTEM (A Study of Law No. 25 Year 2004 About the National Development Planning System) - Andi Aminah (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal